WHO AM â€œIâ€ IN ACADEMIC WRITING?: THE STUDY OF AUTHORIAL IDENTITY - Asprillia, Anandya; Hardjanto, Tofan Dwi (LLT Journal: A Journal on Language and Language Teaching, 2020)
In this paper, we attempt to examine the identity of researchers in writing their research articles (RAs) by exploring the linguistic forms indicating the identity of the authors in English RAs, determining the functions these forms serve in the discourse, and revealing the socio-cultural aspects implied from the use of the authorial identity. We will identify the English first-person pronouns used by native and non-native authors in Scopus-indexed linguistics and education academic journal articles. This study applied the corpus linguistic method to collect the data and to draw conclusions about the authorial identity presented in the articles. Hopefully, this paper will help to not only comprehend the role and the importance of the authorial presence but also encourage researchers to represent their identity in their own RAs.DOI: doi.org/10.24071/llt.2020.230110